Partial pancreatic transdifferentiation of primary human hepatocytes in the livers of a humanised mouse model. (16th April 2018) - Ren, Binhai; La, Que T.; O'Brien, Bronwyn A.; Nassif, Najah T.; Tan, Yi; Gerace, Dario; Martiniello‐Wilks, Rosetta; Torpy, Fraser; Dane, Allison P.; Alexander, Ian E.; Simpson, Ann M.
Abstract: Background: Gene therapy is one treatment that may ultimately cure type 1 diabetes. We have previously shown that the introduction of furin‐cleavable human insulin (INS‐FUR) to the livers in several animal models of diabetes resulted in the reversal of diabetes and partial pancreatic transdifferentiation of liver cells. The present study investigated whether streptozotocin‐diabetes could be reversed in FRG mice in which chimeric mouse‐human livers can readily be established and, in addition, whether pancreatic transdifferentiation occurred in the engrafted human hepatocytes. Methods: Engraftment of human hepatocytes was confirmed by measuring human albumin levels. Following delivery of the empty vector or the INS‐FUR vector to diabetic FRG mice, mice were monitored for weight and blood glucose levels. Intraperitoneal glucose tolerance tests (IPGTTs) were performed. Expression levels of pancreatic hormones and transcription factors were determined by a reverse transcriptase‐polymerase chain reaction (RT‐PCR) and immunohistochemistry. Results: Diabetes was reversed for a period of 60 days (experimental endpoint) after transduction with INS‐FUR. IPGTTs of the insulin‐transduced animals were not significantly different from nondiabetic animals. Immunofluorescence microscopy revealed the expression of human albumin and insulin in transduced liver samples. Quantitative RT‐PCR showed expression of human and mouse endocrine hormones and β‐cell transcription factors, indicating partial pancreatic transdifferentiation of mouse and human hepatocytes. Nonfasting human C‐peptide levels were significantly higher than mouse levels, suggesting that transdifferentiated human hepatocytes made a significant contribution to the reversal of diabetes. Conclusions: These data show that human hepatocytes can be induced to undergo partial pancreatic transdifferentiation in vivo, indicating that the technology holds promise for the treatment of type 1 diabetes.